Ascending aorta and aortic root replacement in an infant: a case report - V. A. Mironenko (Патология кровообращения и кардиохирургия, 2021)
We herein report the first clinical case of prosthetic replacement of the ascending aorta and aortic arch to repair a giant aneurysm in a 7-month-old child. The ascending aorta and arch replacement to the level of left subclavian artery was performed using a no. 16 Polymaille prosthesis, the brachiocephalic trunk was reimplanted into the vascular prosthesis and the kinked section of the left common carotid artery was removed, followed by reimplanting the left common carotid artery into the left subclavian artery. First, proximal anastomosis with the vascular prosthesis was created using a no. 16 Polymaille prosthesis and the vascular suture was strengthened with a Teflon strip. During circulatory arrest, the aortic arch was crossed between the orifice of the left common carotid artery and left subclavian artery, with the cut extended to the isthmus region along the small curvature of the arch. The brachiocephalic trunk was aligned and brought down, with subsequent implantation into the ascending aorta prosthesis 2 cm below the initial fixation point. In the final stage, the kinked section of the left common carotid artery was resected and the aligned left carotid artery was directly reimplanted into the left subclavian artery using end-to-side anastomosis. The patient developed tracheobronchitis and moderate heart failure during the postoperative period. The duration of mechanical ventilation was 16 hours. Infusion and antibacterial therapy were discontinued on postoperative day 8. On postoperative day 13, the patient was discharged and referred to the outpatient centre for further treatment and rehabilitation. A sufficiently large-sized prosthesis allows for further development in paediatric patients. This is facilitated by the preservation of the native aortic root with restored valve function and the formation of a bevelled distal anastomosis with a small unchanged aortic section in the isthmus region, which maintains growth potential. This first reported case of an infant demonstrates the possibility of combination interventions on the aortic arch and brachiocephalic artery during the first year of life. Received 30 January 2021. Revised 24 March 2021. Accepted 29 March 2021. Funding: The study did not have sponsorship. Conflict of interest: The authors declare no conflicts of interests. Contribution of the authors: The authors contributed equally to this article.